Phytochemical Screening of Petroleum Ether Fractions by GC/MS and Isolation of Lupeol from Two Different Parts of Iraqi Leucaena leucocephala. (Conference Paper )# - Satar_Al_Baaj, Azal (Iraqi Journal of Pharmaceutical Sciences, 2023)
Abstract This work is considered the first study for the components of the Iraqi Leucaena leucocephala plant, where the different phytochemical compounds that present in the aerial parts were identified by using the gas chromatography/mass spectrometry technique (GC/MS). The type of the components and their concentration will differ according to the part of the plant used and the method of extraction (hot and cold). This study made a comparison in lupeol concentration that was identified and isolated from petroleum ether fractions of Leucaena leucocephala by using Gas Chromatography/Mass Spectrometry (GC/MS), High-performance thin-layer chromatography (HPTLC), and Preparative High-Performance Liquid Chromatography (P-HPLC). The plant leaves and stems were collected in September, dried under shade, and powdered (separately), then extracted by two extraction methods: hot Soxhlet and cold maceration method using 85% ethanol, then the result crude extract was fractionation with petroleum ether by using a separator funnel. The results of GC/MS, HPTLC, and PHPLC indicated that the leaves contain a higher concentration of lupeol than the stems and the cold maceration method is more efficient than the hot Soxhlet extraction method. Lupeol has many pharmacological activities applied in alternative medicine such as anti-inflammatory, antimicrobial, anti-arthritic, anticancer, antidiabetic, and antioxidant activities with wide future applications.